Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

Understanding patient barriers and enablers to accessing community resources: a qualitative study to inform navigation service delivery - Saluja, Kiran; Mahbub, Adiba; Gauthier, Alain P.; Lemonde, Manon; Timony, Patrick; Durand, François; Dahrouge, Simone (BMC Primary Care, 2025)
Abstract Background Individuals face multifaceted barriers to accessing community resources, which can significantly impact their ability to obtain necessary support and services. This study examines barriers and enablers to access community resources among primary care patients and explores the interplay between individual- and system-level factors that influence access to resources. Methods In this qualitative study, we conducted 32 semi-structured interviews with primary care patients who participated in a social prescribing trial that compared two navigation services: ARC (patient-centered longitudinal support) vs. Ontario-211 (free 24-hour helpline service) in two regions, Ottawa and Sudbury, in the province of Ontario, Canada. We conducted thematic data analysis with a deductive/inductive hybrid approach, employing Levesque’s theoretical framework for access to health that examines the various system and individual level factors influencing access to healthcare services. Findings At the system level, various systemic barriers encompassing broader organisational, structural, and policy-related elements influenced patients' access to community resources (outreach, availability, location, costs and accommodations for patient needs and preferences). These factors directly interacted with various patient-level factors (awareness of needs, ability to seek support, to reach resources and to pay for those, their physical and mental health, motivation, and confidence to engage in care) to determine access. Conclusions Our findings highlight individual- and system-level barriers and enablers for accessing community resources among socially complex primary care patients with multiple unmet needs. As governments and organizations in Canada are increasingly investing in community-based services to address adverse social determinants of health (SDH), an upstream approach that reduces both systemic and individual-level barriers to access is warranted. Language significantly influences access to services, particularly for linguistic minorities (see page 5 and 7)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)